2002
DOI: 10.1046/j.1365-8711.2002.05558.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2dF Galaxy Redshift Survey: the environmental dependence of galaxy star formation rates near clusters

Abstract: We have measured the equivalent width of the Hα emission line for 11 006 galaxies brighter than Mb=−19 (ΩΛ= 0.7, Ωm= 0.3, H0= 70 km s−1 Mpc−1) at 0.05 < z < 0.1 in the 2dF Galaxy Redshift Survey (2dFGRS), in the fields of 17 known galaxy clusters. The limited redshift range ensures that our results are insensitive to aperture bias, and to residuals from night sky emission lines. We use these measurements to trace μ*, the star formation rate normalized to L*, as a function of distance from the cluster centre, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

62
616
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 711 publications
(686 citation statements)
references
References 61 publications
62
616
8
Order By: Relevance
“…The inferred quenching timescales were therefore long, roughly a few Gyrs, which is comparable to the cluster crossing time. This conclusion is in agreement with Lewis et al (2002) and Gómez et al (2003) who note the existence of galaxies with low specific star formation rates at large distances from the centres of clusters and conclude that rapid environmental quenching alone cannot explain the population of galaxies seen in the local Universe.…”
Section: Introductionsupporting
confidence: 92%
“…The inferred quenching timescales were therefore long, roughly a few Gyrs, which is comparable to the cluster crossing time. This conclusion is in agreement with Lewis et al (2002) and Gómez et al (2003) who note the existence of galaxies with low specific star formation rates at large distances from the centres of clusters and conclude that rapid environmental quenching alone cannot explain the population of galaxies seen in the local Universe.…”
Section: Introductionsupporting
confidence: 92%
“…Previous studies (Lewis et al 2002;Gray et al 2004;Rines et al 2005;Verdugo et al 2008) have similarly found that star formation of galaxies within infall regions remains suppressed compared to the field out to radii of ∼ 2 − 3 R 200 . This suppression is often attributed to backsplash galaxies which have already made a passage through the halo centre, the pre-processing of galaxies in small groups prior to infall, or some combination of the two.…”
Section: Galaxy Properties At Large Radiimentioning
confidence: 87%
“…The flow of gas into and out of galaxies within clusters, and into the cluster itself, is strongly affected by the cluster environment. Our understanding of the competing processes involved is still forming, from galaxy level processes such as galactic outflows and inflows to cluster specific processes such as rampressure stripping, galaxy mergers, galaxy harassment, and starvation (e.g., Cayatte et al, 1990;Vollmer et al, 2001; Lewis et al, 2002;Roediger & Hensler, 2005;Chung et al, 2007;Tonnesen, Bryan & van Gorkom, 2007;Yoon et al, 2012). In addition, our understanding of gas flows onto clusters from IGM filaments is incomplete.…”
Section: Introductionmentioning
confidence: 99%